Home visits and nursing home visits by early-career GPs: a cross-sectional study. (14th September 2016) - Magin, Parker; Catzikiris, Nigel; Tapley, Amanda; Morgan, Simon; Holliday, Elizabeth G; Ball, Jean; Henderson, Kim; Elliott, Taryn; Regan, Cathy; Spike, Neil
Abstract: Background: Home visits (HVs) and nursing home visits (NHVs) are accepted as core elements of general practice. There is concern regarding declining rates of HVs and an increasing demand for NHVs together with a perceived decreased willingness of younger GPs to provide these services. Objectives: To establish the prevalence and associations of recently vocationally qualified GPs ('graduates') performing HVs and NHVs. Methods: A cross-sectional questionnaire-based study of recent (within 5 years) graduates of 3 of Australia's 17 regional general practice training programs. Outcome factors were performing, as part of current practice, HVs and NHVs. Factors associated with each outcome were assessed by logistic regression with graduate and current practice characteristics and vocational training experiences as independent variables. Results: Of 230 responding graduates, 48.1% performed HVs and 40.6% performed NHVs in their current clinical GP role. Factors associated with both HVs and NHVs were participating in in-practice clinical teaching/supervision [odds ratios (ORs) 2.65 and 2.66], conducting HVs/NHVs during training (ORs 5.05 and 10.8) and working full-time (ORs for part-time work 0.20 and 0.29). Further associations with performing HVs were older GP age (compared to <36 years: ORs 3.65 for 36–40 and 2.53 for 41+), smaller practice size (OR 0.53 for larger practices), Australian undergraduate education (OR 0.31 for non-Australian) and greater number of years in their current practice as a qualified GP (OR 1.25 per year). Conclusions: Our findings of graduates' modest engagement with HVs and NHVs reinforce concerns regarding Australian general practice's capacity to accommodate the needs of an aging population.